What are we doing when we perceive numbers?. (15th December 2021) - Jones, Max; Zahidi, Karim; Hutto, Daniel D.
Abstract: Clarke and Beck rightly contend that the number sense allows us to directly perceive number. However, they unnecessarily assume a representationalist approach and incur a heavy theoretical cost by invoking "modes of presentation." We suggest that the relevant evidence is better explained by adopting a radical enactivist approach that avoids characterizing the approximate number system (ANS) as a system for representing number.